The effect of ginger and garlic on the microbial load and shelf life of Kunun-zaki - Edward, K.C., Ohaegbu, C.G. (Journal of Applied Pharmaceutical Science)
Kunun-zaki was produced using ginger and garlic and stored under ambient conditions for 10 days. The microbiological load and the shelf life of the drink were investigated. Diverse microbial genera: Lactobacillus, Bacillus, Staphylococcus, Aspergillus, Penicillum, Fusarium and Saccharomyces were isolated from samples. The effect of ginger and garlic separately were compared to the combined effect of ginger and garlic in reducing the microbial population. Of all the treatments, garlic (2g in 200mls or 0.01%w/v) was most effective in reducing the microbial populations. In contrast, treatment with 1g of ginger was least effective in reducing the microbial populations. Shelf life based on sensory overall acceptability and microbial quality of the samples varied with treatments but combination treatment with 2g in 200mls(0.01%w/v) ginger and garlic extended the shelf life by approximately four (4) days whereas other treated samples showed marginal enhanced shelf life of 2days. However, untreated control sample exhibited remarkably high microbial load and was virtually unacceptable after 24h of production. The result shows the potential of the combination treatment of ginger and garlic as antimicrobials and in extending the shelf life of Kunun-zaki.
Keywords: Kunun-zaki, ginger, garlic, shelf life, microbial load.